Pendampingan UMKM Berbasis E-Commerce dan Packaging di Desa Mancak Kabupaten Serang - Ichsan Adil Prayogi; R Nia Kania Kurniawati; Delly Maulana (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2023)
This research is motivated by community service activities (student work lectures) carried out by Serang Raya University students, where one of the main targets is to find out how business communication is carried out by MSMEs Onion sticks from Mancak Village and to improve MSMEs to become more advanced. By using qualitative research methods and a case study approach, using Fatimah, who is the founder of this UMKM, and Febby Fitriani as the owner, the author finds that the UMKM Sticks of Mancak Village initially only used interpersonal communication by entrusting their products to stalls. around. Since it was founded in 2015, it was only in 2022 or to be precise after the service activities carried out by Serang Raya University students, this Stick MSME began rejuvenation with new packaging which had a positive impact on increasing product sales. In 2022, MSME Onion Sticks will start selling via the e-commerce Shopee, but with the complexity of e-commerce tools and the need for the latest or additional gadgets, therefore marketing through e-commerce has not run optimally. The SWOT analysis is also attached at the end of the discussion to provide positive input for the MSME Sticks of Mancak Village, particularly, and MSMEs for food products in general